Protocolo de elección de tratamiento antifibrótico en Albacete - Godoy R; Sánchez R (Revista SOCAMPAR, 2017)
Resume: Diffuse Interstitial Lung Diseases are uncommon pathologies. Among them the Idiopathic Pulmonary Fibrosis has an unfortunate prognosis, and had no treatment until a few years ago. Given the high cost of this treatment and its side effects and interactions, it is essential to establish a correct choice of antifibrotic treatment, when this is necessary.